Microstructural evolution in the cross section of Ni-based superalloy induced by high power laser shock processing. (September 2021) - Cao, Jiangdong; Cao, Xueyu; Jiang, Bochen; Yuan, Fang; Yao, Da; Huang, Jian
Highlights: Microstructural evolution of cross-sections was revealed after LSP. Low-angle grain boundaries, twins and motion of dislocations were characterized. Slip and twinning of crystals in cross-sections were observed during LSP. The multisystem slippage induced by LSP promoted the refinement of grains. Abstract: Microstructural evolution in the cross-section of Ni-based superalloy GH202 treated by high power laser shock processing (LSP) were investigated. The microstructures on surfaces and cross-sections of alloy specimens were characterized by electron backscatter diffraction and transmission electron microscopy. The results showed that dislocation slip and twinning were generated simultaneously during plastic deformation induced by high power LSP, with many low-angle grain boundaries and twins produced in the surface. The dynamic recrystallization occurred at the spot overlap after LSP due to the crystal migration and subgrain rotation. The dislocation multiplication promoted dislocations to pile up and form dislocation stacking and tangling in the subsurface. The multisystem slippage occurred in the plastic deformation induced by LSP from 40 to 130 μm depth and the motion of dislocation lines in two or more slip systems formed dislocation arrays and subgrains. In areas over 200 μm depth from the surface, dislocation density significantly decreased and a small amount of subgrains and dislocation cells remained. Therefore, LSP had a positive effect on grain refinement, formation of low-angle grain boundaries, and mechanical property improvements.